2013
DOI: 10.1177/0956462413484457
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection in patients infected with human immunodeficiency virus in an endemic area in Iran

Abstract: Some studies have suggested that hepatitis E virus is more frequent in human immunodeficiency virus (HIV) patients and can progress to chronic infection. We aimed to determine the prevalence of hepatitis E virus antibodies and RNA in a series of 100 HIV-infected patients in Tehran, Iran, with comparison to 52 healthy HIV, hepatitis B and C-negative blood donors as controls. HIV-infected patients were also tested for hepatitis E virus-RNA. Among the HIV-infected patients, 10% had antibodies to hepatitis E virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…Similarly, two other studies conducted in Argentina also noted a higher seroprevalence among HIV-infected individuals (6.6% and 7.3%) compared to blood donors (1.8%) and HIV-negative individuals (4.4%), possibly related to blood transmission (Fainboim et al, 1999) or to lower CD4 counts (Debes et al, 2016). However, other studies have found no differences in prevalence between these two population groups (Politou et al, 2015;Ramezani et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, two other studies conducted in Argentina also noted a higher seroprevalence among HIV-infected individuals (6.6% and 7.3%) compared to blood donors (1.8%) and HIV-negative individuals (4.4%), possibly related to blood transmission (Fainboim et al, 1999) or to lower CD4 counts (Debes et al, 2016). However, other studies have found no differences in prevalence between these two population groups (Politou et al, 2015;Ramezani et al, 2013).…”
Section: Discussionmentioning
confidence: 72%
“…This disorder is sometimes attributable to drug-induced liver injury [24] or metabolic abnormalities [23]. In areas where this topic has been investigated, the prevalence of HEV seropositivity was similar in HIVinfected people and in control groups [5,10]. Because of this, clinicians should be aware of hepatitis E as a possible source of chronic liver damage, but systematic screening for this agent is not warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, HEV infection may become chronic and rapidly evolve to cirrhosis [3,4]. Several cross-sectional studies have reported prevalence figures of HEV seropositivity in HIV-infected patients ranging from 1.5% in Paris to 45.3% in Ghana [5][6][7][8][9][10]. Studies including a HIV-seronegative control population [5,10] did not find differences in the rate of HEVexposure between HIV-infected patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…When HCV viral load is high we predict liver fibrosis, thus it can be stated that HEV coinfected whit HCV may cause further damage the liver and progression to liver cancer. This examination proved that the most infected patients belonged to low levels of literacy section and urban residents, which some previous studies (18). Thus, the absence of enough information about endemic HEV, the low level of public awareness of the disease and transmission of HEV through fecal-oral were the main reasons for high prevalence among the population.…”
Section: Discussionmentioning
confidence: 93%